Overcoming Family Hardships in Akhil Sharma's Novel Family Life (2014) - Fikha Rahmadina; Desvalini Anwar (English Language and Literature, 2022)
The purpose of this analysis is to expose the issue of overcoming life hardships in the novel Family Life (2014) by Akhil Sharma. The issue of overcoming life hardships refers to the types of life hardships that the immigrants face and efforts that the immigrants take to overcome the life hardships from the main character’s perspective. This analysis looks on the hardships of all the characters inside the novel which are having brain-damaged family member and having alcoholic family member. The two efforts that the characters make to overcome the hardships are accepting the condition of brain-damaged family member and helping the alcoholic member to sober. This analysis is related to the concept of life instinct which proposed by Sigmund Freud. The use of the concept is based on the interpretation of text and context of the novel. This analysis also uses a lot of fictional devices such as character, plot, and setting to reveal the meaning. The result of the study shows that the characters have desire to solve their problems and they are also persistent and strong even though they find another problem to solve.